Exploring Muslim Pre-Service Teachers’ Honesty on Cheating and Plagiarism: A Survey in Indonesian Islamic University - Rafika Rabba Farah (Dinamika Ilmu, 2021)
Cheating and plagiarism have been crucial issues among students studying either at high school or undergraduate levels. This present study aims to reveal the cheating and plagiarism practices among pre-service teachers in their undergraduate program at one Islamic university in Indonesia. As Muslim teacher candidates, the respondents are urged to uphold academic integrity and honesty. Thus, this study seeks to provide data on how serious the academic ethics immersed in Muslim pre-service teachers. The method implemented for this study was a cross-sectional survey. The respondents were students enrolled in the Faculty of Education, which comprises several departments in the education fields. Results indicate that respondents were recorded as having morally ethical on one aspect of academic integrities, 95% never paid someone else for the exam, 75% never changed answers after the marking process, and 50% declared rarely copy an answer. Yet, there was also a display of less ethical attitude on some other academic behaviors driven by cultural factors. Thus, some teaching implications are highlighted for teachers and students to combat cheating and plagiarism practices among pre-service teachers in Indonesian Islamic universities.